1983
DOI: 10.1203/00006450-198308000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Early Weanling and Precocious Development of Small Intestine in Rats: Genetic, Dietary or Hormonal Control

Abstract: Summary14); however, its relationship to diet has been explored only to a Small intestinal development was followed in rats from 17 to 28 days of age in order to evaluate the interactions of diets, genetic preprogramming, and hormones in influencing developmental changes. Control pups, weaned naturally at 21-24 days, showed a gradual increase in body weight, intestinal length, and segmental mucosal weight, total DNA, and protein content. In contrast, pups weaned at 17 days showed an immediate increase in intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
8

Year Published

1984
1984
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 22 publications
4
26
0
8
Order By: Relevance
“…Early weaning in rats has been shown to induce precocious expression of sucrase activity, a marker of intestinal differentiation [19, 20]. A study by Lebenthal et al [21]also demonstrated the precocious increases of sucrase activity in suckling rat pups fed with sucrose-containing diet.…”
Section: Discussionmentioning
confidence: 90%
“…Early weaning in rats has been shown to induce precocious expression of sucrase activity, a marker of intestinal differentiation [19, 20]. A study by Lebenthal et al [21]also demonstrated the precocious increases of sucrase activity in suckling rat pups fed with sucrose-containing diet.…”
Section: Discussionmentioning
confidence: 90%
“…In rats, corticosteroids are considered as mediators of pancreatic amylase activity development in early weaning (Lee & Lebenthal, 1983b) and in calves the pancreatic activities might be at least partly modulated by gastrin in the first weeks of life (Le Huerou-Luron et al, 1992). When some data are available in this field, they mostly concerned the weaning period (Lee & Lebenthal, 1983a;Henning, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Os mecanismos que coordenam o crescimento e desenvolvimento órgãos podem ser influenciados por fatores genéticos, hormonais e de dietas 121 .…”
Section: Desmame Precoceunclassified